Disuse Impairs the Mechanical Competence of Bone by Regulating the Characterizations of Mineralized Collagen Fibrils in Cortical Bone - Yang, Peng-Fei; Nie, Xiao-Tong; Wang, Zhe; Al-Qudsy, Luban Hamdy Hameed; Ren, Li; Xu, Hui-Yun; Rittweger, Joern; Shang, Peng (Frontiers in Physiology, 2019)
Bones are made of complex material comprising organic components and mineral hydroxyapatite, both of which formulate the unique hierarchical structure of bone and its mechanical properties. Bones are capable of optimizing their structure and mechanical properties according to the mechanical environment. Mineral loss is a well-known consequence of skeleton disuse. By contrast, the response of the non-mineral phase of bone, i.e., the collagen network, during disuse remain largely unknown. In this study, a tail-suspension mice model was used to induce bone loss. Atomic force microscopy-based imaging and indentation approaches were adopted to investigate the influence of disuse on the morphology and in situ mechanical behavior of the collagen fibrils, under both non-loaded and load-bearing conditions, in the cortical tibia of mice. The results indicate that disuse induced by hindlimb unloading did not alter the orientation and D-periodic spacing of the collagen fibril, but results in decreased collagen crosslinking which correlates with decreased elasticity and increased susceptibility to mechanical damage. More concretely, the collagen fibrils in the disused tibia were misaligned under mechanical loading. It therefore indicates that the disordered arrangement of the mineralized collagen fibrils is one of the characteristics of the weakened bone during elastic deformation. These findings reveals the unique adaptation regimes of the collagen fibrils in the cortical bone to disuse, as well as the deformation mechanisms of bone in the relevant pathological process at different scales.